Efficacy of an Asynchronous Tele-Medicine Model in Otorhinolaryngology - Gyawali, Bigyan Raj; Chalise, Ganesh Bahadur; Obaidullah, Obaidullah; Ghimire, Saurav; Kashyap, Ashutosh (Journal of Institute of Medicine Nepal, 2025)
Introduction Access to Otorhinolaryngologists in remote regions is limited in Nepal. The country’s rugged topography is one important cause. Telemedicine may help bridge this gap; however, evidence supporting its effectiveness in low-resource settings is sparse. This study evaluates the diagnostic performance of an asynchronous telemedicine model in Otorhinolaryngology at Tribhuvan University Teaching Hospital. Methods A hospital-based analytical cross-sectional study was conducted in a tertiary care center. A convenience sampling method was used with a minimum sample of 94., The study included patients of all ages. Trained undergraduate medical students recorded the clinical history and examination findings of the participants. Diagnoses made through asynchronous telemedicine using smartphones, endoscopic imaging, and EMR systems by a consultant Otorhinolaryngologist were compared with standard in-person evaluations in 102 patients by a separate ENT specialist independently. Concordance was assessed using Cohen’s Kappa. Results Diagnostic agreement analysis showed high diagnostic concordance across Otorhinolaryngology subspecialties; rhinology had the highest concordance (κ = 0.96) followed by pediatric cases (κ = 0.84), Otology cases (κ = 0.79), and then head and neck cases (κ = 0.79). Diagnostic discrepancies arose mainly due to poor-quality images and the lack of physical examination. Conclusion Asynchronous telemedicine is a viable strategy for otolaryngology diagnostics in resource-constrained settings. It holds potential to improve access to specialist care and optimize referral efficiency in Nepal and similar contexts.